Profound morphological and functional changes of rodent Purkinje cells between the first and the second postnatal weeks: a metamorphosis? - Dusart, Isabelle; FLAMANT, Frédéric (Frontiers in Neuroanatomy, 2012)
Between the first and the second postnatal week, the development of rodent Purkinje cells is characterized by several profound transitions. Purkinje cells acquire their typical dendritic “espalier” tree morphology and form distal spines. During the first postnatal week, they are multi-innervated by climbing fibers and numerous collateral branches sprout from their axons, whereas from the second postnatal week, the regression of climbing fiber multi-innervation begins, and Purkinje cells become innervated by parallel fibers and inhibitory molecular layer interneurons. Furthermore, their periods of developmental cell death and ability to regenerate their axon stop and their axons become myelinated. Thus a Purkinje cell during the first postnatal week looks and functions differently from a Purkinje cell during the second postnatal week. These fundamental changes occur in parallel with a peak of circulating thyroid hormone in the mouse. All these features suggest to some extent an interesting analogy with amphibian metamorphosis.